2018
DOI: 10.12669/pjms.344.14127
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism among local adult obese population

Abstract: Objective:To determine the frequency of subclinical hypothyroidism in local adult obese population.Methods:The study was conducted at Hayatabad Medical Complex, Peshawar, from March, 2017 to August, 2017. All patients aged between 18 and 60 years with BMI of more than 29kg/m2 were included in the study. Patients on lipid lowering drugs, with renal failure, hepatic failure and already diagnosed cases of thyroid dysfunction were excluded from the study. Thyroid functions were measured for all patients.Results:A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…When TSH binds to the receptor in adipocytes, it stimulates interleukin-6 release from adipocytes and then mediates proliferation, differentiation, and leptin secretion of preadipocytes and adipocytes [16]. The growing evidence also suggests an association of altered thyroid function and obesity causes a lasting state of low-grade inflammation, while Nayak et al found no association between obesity and subclinical hypothyroidism among PCOS patients [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…When TSH binds to the receptor in adipocytes, it stimulates interleukin-6 release from adipocytes and then mediates proliferation, differentiation, and leptin secretion of preadipocytes and adipocytes [16]. The growing evidence also suggests an association of altered thyroid function and obesity causes a lasting state of low-grade inflammation, while Nayak et al found no association between obesity and subclinical hypothyroidism among PCOS patients [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been published with data that even unit change in TSH level can alter the components of fat metabolism by 3%. 13,14 Thyroid hormones have an association with weight and adipose tissue. Hypothyroidism is associated with a decrease in metabolic rate and affects both lipid and carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in metabolic activities and thermal regulation leading to increased weight gain and obesity are usually consequences of hypothyroidism. Previous investigations have referred to a potential association between subclinical hypothyroidism and weight gain, through the potential effects on lipid metabolism, which can eventually increase the risk of cardiovascular diseases as well (Figure 1 ) [ 38 - 39 ]. On the other hand, patients with hyperthyroidism usually suffer from weight loss, although it has been frequently reported that these patients usually have increased appetite and energy production [ 40 ].…”
Section: Reviewmentioning
confidence: 99%